TINGKAT KEJADIAN INFEKSI Ancylostoma sp. PADA ANJING UMUR KURANG DARI 6 BULAN DI YOGYAKARTA - , WAHYU EKA STYAWAN; , drh. Hary Purnamaningsih, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Ancylostomiasis parasitic disease caused by nematodes which infest on adult dog or young dog, mainly on puppy. The infected dog show clinical signs, such as dyspnoe, anemia, anorexia, potbelly, emaciated, and there is time when the intestine get obstruct by the nematode and causing diarrhea. This study aimed to determined the incidence level of Ancylostoma sp. infection on puppy under 6 month old in Yogyakarta. A houndred feces samples taken from dogs and puppys in Yogyakarta. Samples examined with native and sentrifuge method at Parasitology Laboratorium and Internal Animal Laboratorium of Faculty Veterinary Science, Gadjah Mada University. The results of the examination separated into two groups, group dogs above 6 month old (50 samples) and dogs under 6 month old (50 samples). The result data analyzed descriptively and statistic Chi-square. The experiment data showed that 41 of 100 samples (41%) were found Ancylostoma sp. eggs. Based in group, 26 of 50 samples of dog under 6 month old (52%) and 15 of 50 samples of dogs above 6 month old (30%) were found Ancylostoma sp. eggs. Based on the result data, it could conclude the incidence of Ancylostoma sp. infection in Yogyakarta was 41%. Infection occur in dogs under 6 month old in bigger (52%) than infection occur in dogs above 6 month old (30%) with incidence level 2,528 bigger of dogs above 6 month old. The owner of the dog suggested to should pay more attention to the dog health and sanitation as well as improve maintenance management at the puppies.